Insights into Cardiovascular Disease Risk Based on Platelet Indices and Lipid Ratios in Reference to Glycemic Control and Duration of Diabetes - Risal, Prabodh; Bhatt, Rajendra Dev; Sakhakarmi, Nikita; Thapa, Saroj; Koju, Surendra (Journal of Nobel Medical College, 2020)
Background: Diabetic patients are at the risk of untimely atherosclerotic cardiovascular disease. The level of blood lipids, their ratios, glycosylated hemoglobin, and platelet indices are potential markers for the assessment of cardiovascular disease risk in diabetic patients. This study aims to insights into cardiovascular disease risk among diabetic patients in reference to glycemic control and duration of diabetes on the basis of lipid ratios and platelet indices by comparing with healthy controls.Materials and Methods: A case control study was carried out among the patients, diagnosed as type 2 diabetes mellitus at Dhulikhel hospital-Kathmandu University hospital. Socio-demographic questionnaire, anthropometric measurements, and biochemical tests was performed. Descriptive analysis and independent T-test for the testing relationship between categorical variables along with correlation was done.Results: Nearly one-third of diabetic patients were under poor glycemic control with high risk of cardiovascular diseases on the basis of blood lipid ratios and platelet indices. Cardiac risk ratio, Atherogenic Index of Plasma, and Atherogenic Coefficient was found to be significantly high in diabetic compared to the control group (5.22±1.54 vs. 3.71±0.99, p